2021
DOI: 10.3390/w13162297
|View full text |Cite
|
Sign up to set email alerts
|

Ice Melt-Induced Variations of Structural and Functional Traits of the Aquatic Microbial Community along an Arctic River (Pasvik River, Norway)

Abstract: The effects of climate change-induced ice melting on the microbial communities in different glacial-fed aquatic systems have been reported, but seasonal dynamics remain poorly investigated. In this study, the structural and functional traits of the aquatic microbial community were assessed along with the hydrological and biogeochemical variation patterns of the Arctic Pasvik River under riverine and brackish conditions at the beginning (May = Ice-melt (−)) and during the ice-melting season (July = Ice-melt (+)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 56 publications
1
7
0
Order By: Relevance
“…Dissolved oxygen, pH, and redox values were 93.9 mg/L, 7.2, and 198 mV, respectively, whereas total dissolved solids were 228 ppm, as it was previously reported by Papale et al (2021). Bacterial community diversity and activities in water and sediment were reported previously (Papale et al, 2021, and Papale, Rizzo, et al, 2022, respectively), along with data on heavy metal (HM)‐pollution and HM‐tolerant cultivable bacterial communities (Caputo et al, 2019) and persistent organic pollutant (POP) concentrations in sediments (Papale, Rizzo, et al, 2022). Data from Papale et al (2021); Papale, Rizzo, et al (2022); and Caputo et al (2019) were used for statistical analyses (see below) and reported in Table S1.…”
Section: Methodssupporting
confidence: 84%
See 2 more Smart Citations
“…Dissolved oxygen, pH, and redox values were 93.9 mg/L, 7.2, and 198 mV, respectively, whereas total dissolved solids were 228 ppm, as it was previously reported by Papale et al (2021). Bacterial community diversity and activities in water and sediment were reported previously (Papale et al, 2021, and Papale, Rizzo, et al, 2022, respectively), along with data on heavy metal (HM)‐pollution and HM‐tolerant cultivable bacterial communities (Caputo et al, 2019) and persistent organic pollutant (POP) concentrations in sediments (Papale, Rizzo, et al, 2022). Data from Papale et al (2021); Papale, Rizzo, et al (2022); and Caputo et al (2019) were used for statistical analyses (see below) and reported in Table S1.…”
Section: Methodssupporting
confidence: 84%
“…At sampling time, sediment and water samples were contextually collected in duplicates within a 10‐cm radius of the sponges (Papale et al, 2021; Papale, Rizzo, et al, 2022). Dissolved oxygen, pH, and redox values were 93.9 mg/L, 7.2, and 198 mV, respectively, whereas total dissolved solids were 228 ppm, as it was previously reported by Papale et al (2021).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sediment samples (25–70 cm depth; except for St. 6) were manually collected from nine stations along the Pasvik River at the beginning and ongoing ice-melting [(i.e., Ice-melt(−): 22–29 May; (Ice-melt(+): 17–24 July)] [ 10 , 13 ] ( Figure 1 ). The stations were classified as riverine (Stations 9, 5, 1, 2, and 8) or brackish (Stations 3, 7, 6, and 4).…”
Section: Methodsmentioning
confidence: 99%
“…Sediments were mainly composed of sand (granulometry fraction between approximately 0.062 and 2 mm) and mud (fraction < 62 µm) [ 10 ]. The major physical–chemical water parameters have been reported elsewhere [ 10 , 13 ].…”
Section: Methodsmentioning
confidence: 99%